Carpal tunnel syndrome in mucopolysaccharidosis I: a registry‐based cohort study. (11th September 2017) - Viskochil, David; Muenzer, Joseph; Guffon, Nathalie; Garin, Christophe; Munoz‐Rojas, M Veronica; Moy, Kristin A; Hutchinson, Douglas T
Abstract : Aim: To characterize carpal tunnel syndrome (CTS) in patients with mucopolysaccharidosis I (MPS I). Method: Data were included for patients with MPS I who had either nerve conduction examination that included a diagnosis of CTS or who had CTS release surgery. Although this represented a subset of patients with CTS in the MPS I Registry, the criteria were considered the most objective for data analysis. Results: As of March 2016, 994 patients were categorized with either severe (Hurler syndrome) or attenuated (Hurler–Scheie or Scheie syndromes) MPS I. Among these, 291 had a CTS diagnosis based on abnormal nerve conduction ( n =54) or release surgery ( n =237). Median ages (minimum, maximum) at first CTS diagnosis were 5 years 2 months (10mo, 16y 2mo) and 9y 11mo (1y 8mo, 44y 1mo) for patients with severe and attenuated MPS I respectively. Most patients had their first CTS diagnosis after MPS I diagnosis (94%) and treatment (hematopoietic stem cell transplant and/or enzyme replacement therapy) (74%). For 11% of patients with attenuated disease, CTS diagnosis preceded MPS I diagnosis by a mean of 7 years 6 months. Interpretation: CTS is a rare complication in pediatric patients and should alert medical care providers to the potential diagnosis of MPS I. Significant delays exist between diagnosis of CTS and MPS I for patients with attenuated disease. What this paper adds: There are significant delays in diagnosing carpal tunnel syndrome (CTS) in patients with mucopolysaccharidosis I (MPS I). Enzyme replacement therapy or hematopoietic stem cell transplant do not prevent the development of CTS. Testing for CTS in patients with MPS I is recommended to prevent irreparable damage. CTS in pediatric patients should alert physicians to potential diagnosis of MPS I. What this paper adds: There are significant delays in diagnosing carpal tunnel syndrome (CTS) in patients with mucopolysaccharidosis I (MPS I). Enzyme replacement therapy or hematopoietic stem cell transplant do not prevent the development of CTS. Testing for CTS in patients with MPS I is recommended to prevent irreparable damage. CTS in pediatric patients should alert physicians to potential diagnosis of MPS I. This article is commented on by White on pages1213–1214 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.